Sosialisasi Early Warning System Longsor di Kelurahan Ngemplak Simongan Kota Semarang - Fitria Maya Lestari; Etika Herdiarti; Sutik Sutik (Jurnal Pengabdian KOLABORATIF, 2025)
Natural disasters are a threat to the people in Semarang City. Especially in areas that have complex topographical characteristics such as in the Ngemplak Simongan village area of Semarang City. Some of these areas are in conditions that have steep slopes and are in cliff areas. The Community Service activities provide socialization related to the landslide Early Warning System. An Early Warning System (EWS) is a system that informs the occurrence of natural disasters. The socialization activity aims to provide knowledge of making a simple EWS that can be made by the affected community in detecting landslides early. The socialization succeeded in increasing the knowledge of how the early warning system works. Residents can understand the necessary EWS components through training, evacuation drills, and EWS tool introduction materials. The data collected showed that the technique used was successful, although there were residents who still did not understand, it could effectively increase residents' knowledge.